Serum Tryptophan-Derived Quinolinate and Indole-3-Acetate Are Associated With Carotid Intima-Media Thickness and its Evolution in HIV-Infected Treated Adults. (6th December 2019) - Boyd, Anders; Boccara, Franck; Meynard, Jean-Luc; Ichou, Farid; Bastard, Jean-Philippe; Fellahi, Soraya; Samri, Assia; Sauce, Delphine; Haddour, Nabila; Autran, Brigitte; Cohen, Ariel; Girard, Pierre-Marie; et al.
Abstract: Background: HIV-infected individuals undergoing effective antiretroviral therapy (ART) present an increased risk of atherosclerotic cardiovascular disease. We identified serum metabolites associated with carotid intima-media thickness (c-IMT) and its evolution. Methods: One hundred forty-three hydrophilic serum metabolites were measured by ultraperformance liquid chromatography coupled with high-resolution mass spectrometry in 49 HIV+ ART+, 48 HIV+ ART-naïve and 50 HIV-negative, age-matched, never-smoking male triads. Metabolites differentially altered between groups ("features") were defined as having a Benjamini-Hochberg-adjusted P value <.05 from a t test and >0.25 log2 absolute mean fold change in metabolite levels. c-IMT was measured across 12 sites at inclusion in all individuals and at the carotid artery (cca) after a median of 5.1 years in 32 HIV+ ART+ individuals. The difference in c-IMT (cross-sectional analysis) and slope of cca-IMT regression/progression per year (longitudinal analysis) for each log10 (area) increase in metabolite level were estimated with linear regression. Results: Compared with HIV-, metabolite features of HIV+ ART+ were increased N6, N6, N6-trimethyl-L-lysine and decreased ferulate and 5-hydroxy-L-tryptophan, whereas features of HIV+ ART-naïve were increased malate, kynurenine, 2-oxoglutarate, and indole-3-acetate and decreased succinate and 5-hydroxy-L-tryptophan. In HIV+ ART+ individuals, quinolinate and/or indole-3-acetate were positively associated with c-IMT ( P < .03), cca-IMT ( P < .03), and cca-IMT progression ( P < .008). These associations were not observed in HIV+ ART-naïve or HIV-negative individuals. In HIV+ ART+ individuals, the metabolites xanthosine and uridine, from nucleotide metabolism, and g-butyrobetaine, from lysine/dietary choline degradation, were also positively or negatively associated with c-IMT and/or cca-IMT (all P < .01), but not its evolution. Conclusions: In these highly selected HIV-positive ART-controlled males, 2 novel metabolites derived from tryptophan catabolism, indole-3-acetate and quinolinate, were associated with c-IMT and its progression.